Forest Pathology in India: Problems and Control Strategies - Singh, Sujan (Indian Forester, 1985)
The paper highlights disease problems of Indian forests and control strategies which have generally been adopted in the country. Diseases in forest and social forestry nurseries may be caused by soil-inhabiting pathogens/ occurring in nearby plantations or natural forests/pathogens inadvertently introduced from other regions of the country or from foreign countries on planting material. In natural forests, heart-rot diseases caused greatest losses inmerchantable timber. Root-rots generally remain in endemic from unless there is some deviation in prescribed management practices. Plantations raised on forest sites suffer most from root-rot pathogens. Sissoo and Casuarina suffer from wilt diseases; former when raised on unsuitable site and the latter when subjected to illicit lopping and injudicious pruning. Poplars subjected to tractor blade injuries in agro-forestry plantations suffer from hear-rots. Exotic trees in plantations suffer from indigenous pathogens as well as from pathogens in advertently introduced into the country. The latter may sometimes cause heavy damage to susceptible indigenous tree species. Most of the serious diseases occurring in forest areas have been recorded in social forestry plantations which in addition may also suffer from diseases present on agriculture crops. In forestry crops, approach towards integrated control measures based on the principles of exclusion, avoidance, eradication and protection is most appropriate. A pethogen may be excluded from a forest area through effective quarantine practices. The principle of avoidance can be practised by refraining from planting of tree species where their pathogens are expected to develop in epidemic form. Eradication of a disease from a particular area can be effected by destruction of infected trees or tree parts/fungal fruit bodies/alternate hosts of rust pathogens. Protection to trees against diseases can be afforded through amendment of silvicultural practices, by giving prophyllactic spray of fungicides, through use of innocuous fungi as protectants and through genetic resistance.